ANÁLISE DAS CARACTERÍSTICAS DE MATERIAIS SUPERFICIAIS EM FUNÇÃO DA APLICAÇÃO DE LODO ESTABILIZADO EM ÁREA DE CULTIVO DE CITRUS, EM ARAGUARI (MG) - Rodrigues, Sílvio Carlos; Silva, Josenilson Bernardo da; Vieira, Wellington Carlos (Caminhos de Geografia, 2001)
This paper presents the results of an evaluation of the main characteristics oflandforms located at Araguari County where stabilized slime have been scatteredover the soil surface. These characteristics have special importance to determinethe soil capacity of assimilation nutrients and other minerals that exist in this kindof slime provided by frigorific.Keywords: relief and toposequence analysis, infiltration capacity, soil materials